2016
DOI: 10.1016/j.marenvres.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

First evaluation of foraminiferal metabarcoding for monitoring environmental impact from an offshore oil drilling site

Abstract: At present, environmental impacts from offshore oil and gas activities are partly determined by measuring changes in macrofauna diversity. Morphological identification of macrofauna is time-consuming, expensive and dependent on taxonomic expertise. In this study, we evaluated the applicability of using foraminiferal-specific metabarcoding for routine monitoring. Sediment samples were collected along distance gradients from two oil platforms off Taranaki (New Zealand) and their physico-chemical properties, fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 72 publications
(102 reference statements)
2
65
1
Order By: Relevance
“…Several protist taxa (diatoms, foraminifera, ciliates and testate amoebae) are already under investigation, or in use as ecological indicators. For example, foraminiferal metabarcoding has been used to assess the impact of activities as diverse as salmon farming (Pochon et al 2015a) and oil and gas exploration (Laroche et al 2016) on the health of aquatic environments. Such studies could greatly improve our ability to assess environmental impacts .…”
Section: Protistsmentioning
confidence: 99%
“…Several protist taxa (diatoms, foraminifera, ciliates and testate amoebae) are already under investigation, or in use as ecological indicators. For example, foraminiferal metabarcoding has been used to assess the impact of activities as diverse as salmon farming (Pochon et al 2015a) and oil and gas exploration (Laroche et al 2016) on the health of aquatic environments. Such studies could greatly improve our ability to assess environmental impacts .…”
Section: Protistsmentioning
confidence: 99%
“…A limited number have also evaluated data from co-extracted eRNA products (e.g., Pawlowski et al, 2014; Pawlowski et al, 2016a; Visco et al, 2015; Dowle et al, 2015; Pochon et al, 2015; Laroche et al, 2016). Because RNA deteriorates rapidly after cell death, eRNA likely provides a more accurate representation of viable communities (Mengoni et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Blazewicz et al (2013) suggested that the relative concentration of RNA in the environment provides a robust indication of the growth and adaptation potential of microbial communities. In general, when environmental metabarcoding studies have used both eDNA and eRNA they have found slightly stronger correlations between community data generated from eRNA and environmental conditions (Pawlowski et al, 2014; Pawlowski et al, 2016a; Visco et al, 2015; Dowle et al, 2015; Pochon et al, 2015; Laroche et al, 2016). However, working with eRNA adds additional complexities and expenses related to sampling and laboratory analysis including extra precaution during sampling, transport and storage to avoid degradation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations